How technostress may affect employee performance in educational work environments - Bourlakis, Michael; Nisar, Tahir M.; Prabhakar, Guru (Elsevier, 2023)
Despite there being a proliferation of research into the relationship between educators and work-related stress, there appears to be a lack of research on how institutions respond to this problem. The development of information and communications technology (ICT) has contributed to extra stress (technostress) in the education sector as the need to use technology increases and technostress develops. Therefore, this research aims to explore the concept, role and effects of technostress in educational work environments. The education sector is one of the top three industries where occupational stress is most present in the UK. With potential consequences such as increased turnover and absenteeism, it can create extremely costly implications for institutions. It is important that educational organisations ensure that levels of technostress are minimised as much as possible in order to prevent these outcomes from occurring. An exploratory qualitative research methodology was used involving forty-five interviews with educators. Findings showed different perspectives and approaches to technostress and revealed role ambiguity, technology in the workplace, work-life balance and organisational perspectives and support including understanding turnover intentions as the main focus areas in relation to the current study of technostress in education.
Keywords: Technostress; Information technology; Stress; Education; Teachers; Role ambiguity; Work-life balance; Turnover